SPIRITUAL RESOURCES AND CONTEMPORARY PROBLEMS: A Report on the Annual International Interreligious Seminar held in New Jersey, March 18-20, 1983 - DeMarco, Michael A (Journal of Dharma, 1983)
In the recessive corridors of differing cultural histories, there remain countless expressions of human attempts to communicate with God. An individual usually seeks advice and help from others in order to ease the burden of any physical, mental and even spiritual endeavour. A grandiose desire, such as the wish to communicate with God, is surely no exception. This was one reason for an International Interreligious Seminar which took place in New Jersey, March 18-20, 1983. The Seminar was jointly organized by the Centre for Indian and Interreligious Studies, Rome, and the Dharmanivas Centre for Interreligious Research, South Orange, New Jersey, U.S.A. At the opening ceremony of the Seminar Dr.Albert Nambiaparambil, Director of CllS, Rome, lit a cotton wick from the centrally placed Oil Lamp. Symbolically, the representatives of various religions who were present there, including the Hindu, Buddhist, Islamic, Chinese, Japanese, Jewish and Christian traditions followed suit.